PUTIN’S UNDERSTANDERS, RUSSIA’S NORMALIZERS: DISCURSIVE PALETTES BEYOND THE WEST – EAST DIVIDE - Makarychev, Andrey (Journal of Regional Security, 2024)
This Forum focuses on a variety of discourses that in one way or another "understand" and normalize the logic of Putin's war against Ukraine. These discourses have different epistemologies – some of them might simply reproduce Russian propagandistic cliches, while others are embedded in – and adjusted to - specific national contexts; some of them emanate from political milieus, while others have academic pedigrees. Of particular interest for the reader is a comparative frame of the Forum that gives floor to European and non-European perspectives on the topic that at some point resonate, engage, and communicate with each other. The authors discuss social and cultural conditions that produce professional and vernacular narratives sympathetic to or compatible with the Russian officialdom, and deploy them in different theoretical contexts – from neorealist to post-colonial.